Boosting the oxygen evolution catalytic performance of perovskites via optimizing calcination temperature. Issue 14 (17th March 2020) - Lin, Qian; Zhu, Yinlong; Hu, Zhiwei; Yin, Yichun; Lin, Hong-Ji; Chen, Chien-Te; Zhang, Xiwang; Shao, Zongping; Wang, Huanting
Abstract : Simultaneous modulation of intrinsic activity and active site numbers via calcination temperature regulation leads to optimal OER performance of perovskites. Abstract : We report a facile and universal strategy with simultaneous modulation of intrinsic activity and active site numbers to optimize the catalytic performance of perovskites via controlling calcination temperature. As a proof-of-concept, the optimized SCF-800 perovskite (SrCo0.5 Fe0.5 O3− δ prepared with a calcination temperature of 800 °C) shows prominent OER activity ( e.g., 327 mV at 10 mA cm −2 on a glassy carbon electrode in 0.1 M KOH), outperforming the benchmark noble-metal RuO2 and ranking the highest among perovskite-based catalysts reported to date. Experimental results reveal that the reduced particle size (increased surface area) due to a lower calcination temperature provides more active sites, and that the favorable electronic structure with high covalency of metal–oxygen bonds, as demonstrated by advanced soft X-ray absorption spectroscopy (sXAS), contributes to the intrinsic activity enhancement. This work provides a new and facile way for improving the catalytic performance via only regulating preparation conditions.